Peritrophic matrix-degrading proteins are dispensable virulence factors in a virulent Melissococcus plutonius strain - Keiko Nakamura (Nature Portfolio, 2021)
Abstract European foulbrood (EFB) caused by Melissococcus plutonius is a major bacterial disease of honey bees. Strains of the causative agent exhibit genetic heterogeneity, and the degree of virulence varies among strains. In bee larvae orally infected with the highly virulent strains, ingested bacterial cells colonize the larval midgut and proliferate within the sac of the peritrophic matrix (PM), a barrier lining the midgut epithelium. However, the barrier is degraded during the course of infection, and M. plutonius cells eventually directly interact with the midgut epithelium. As M. plutonius possesses genes encoding putative PM-degrading proteins (enhancin, a chitin-binding domain-containing protein and endo-α-N-acetylgalactosaminidase), we constructed PM-degrading protein gene-knockout mutants from a highly virulent M. plutonius strain and investigated their role in the pathogenesis of EFB. In larvae infected with the triple-knockout mutant, which has no PM-degrading protein genes, M. plutonius that proliferated in the larval midguts was confined to the sac of the PM. However, the midgut epithelial cells degenerated over time, and the mutant killed approximately 70–80% of bee brood, suggesting that although the PM-degrading proteins are involved in the penetration of the PM by M. plutonius, they are not indispensable virulence factors in the highly virulent M. plutonius strain.